2013
DOI: 10.1111/1574-6968.12191
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for xylooligosaccharide utilization inWeissellastrains isolated from Indian fermented foods and vegetables

Abstract: Six strains isolated from fermented food were identified as Weissella species by 16S rDNA sequencing, clustering with the species pair W. confusa/W. cibaria. The strains were analysed for growth on glucose, xylose and xylooligosaccharides (XOS). All strains were xylose positive using the API CHL 50 test. Growth on XOS was observed for strains 85, 92, 145 and AV1, firstly by optical density measurements in microtitre plates and secondly in batch cultures also confirming concomitant decrease in pH. Analysis of X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…The β‐xylosidase activity in the Weissella genus was first found by Patel et al . () and confirmed by Immerzeel et al . ().…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The β‐xylosidase activity in the Weissella genus was first found by Patel et al . () and confirmed by Immerzeel et al . ().…”
Section: Introductionsupporting
confidence: 77%
“…In the enzymatic hydrolysis process for hemicellulose, the b-xylosidase should have a high tolerance for glucose and xylose. The b-xylosidase activity in the Weissella genus was first found by Patel et al (2013) and confirmed by Immerzeel et al (2014). Using the Weissella sp.…”
Section: Introductionmentioning
confidence: 92%
“…Evidence for XOS utilization by Leuconostoc lactis (45) and Weissella sp. (46) has been previously reported.…”
Section: Discussionmentioning
confidence: 78%
“…cibaria, W. confusa and W. paramesenteroides have been isolated from fermented leek, fermented cabbage, fermented cauliflower and sauerkraut [63,65,67,119]. These species but also W. soli, W. thailandensis, W. hellenica, W. koreensis, W. minor, W. halotolerans and W. jogaejeotgali have been isolated from Asian traditional fruits and vegetables-based fermented products, like Kimchi, Yan-dong-gua, Pobuzihi, Jiang-gua, Yan-tsai-shin, Yan-jiang, Yan-taozih, Xi-gua-mian, Dochi, Suan-tsai, Jeotgal and Stinky tofu (Table 2) [29,36,[41][42][43][44][46][47][48][49][50][51][52][53][54]56,57].…”
Section: Fruits and Vegetables-based Productsmentioning
confidence: 99%